2018
DOI: 10.1039/c8mh00715b
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous photo(electro)catalysis with eumelanin thin films

Abstract: We report that eumelanin, the ubiquitous natural pigment found in most living organisms, is a photocatalytic material. Though the photoconductivity of eumelanin and its photochemical reactions with oxygen have been known for some time, eumelanins have not been regarded as photofaradaic materials. We find that eumelanin shows photocathodic behavior for both the oxygen reduction reaction and the hydrogen evolution reaction. Eumelanin films irradiated in aqueous solutions at pH 2 or 7 with simulated solar light p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…1 These demands motivated us to explore the possibility of peroxide evolution catalyzed by abundant biomaterials. The present study was guided by recent findings that organic carbonyl dyes 16 and pigments 17 as well as the structurally-related biopolymer eumelanin 18 are photocatalysts for selective reduction of oxygen to peroxide. Lignin shares critical structural features with these proven catalytic speciesnamely aromatic conjugated units with quinone/ hydroquinone redox moieties.…”
Section: Introductionmentioning
confidence: 99%
“…1 These demands motivated us to explore the possibility of peroxide evolution catalyzed by abundant biomaterials. The present study was guided by recent findings that organic carbonyl dyes 16 and pigments 17 as well as the structurally-related biopolymer eumelanin 18 are photocatalysts for selective reduction of oxygen to peroxide. Lignin shares critical structural features with these proven catalytic speciesnamely aromatic conjugated units with quinone/ hydroquinone redox moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Both oxygen reduction reactions are thermodynamically more favorable than hydrogen evolution, with the two-electron peroxide reaction being 700 mV lower than H 2 production. The dominance of the oxygen reduction reaction with organic semiconductors was shown in electrochemical (Warczak et al, 2018;Mitraka et al, 2019), photoelectrochemical (Jakešová et al, 2016;Gryszel et al, 2018a), and photochemical experiments (Gryszel et al, 2018b(Gryszel et al, , 2019 for a wide range of organic semiconductors, including polythiophenes like P3HT, the biopolymer melanin (Migliaccio et al, 2018), and various carbonyl pigments (Gryszel et al, 2018a). The oxygen reduction products are considered reactive oxygen species (ROS) and have numerous physiological effects ranging from toxicity at high concentrations (Huang et al, 2013) to ion channel modulation (Gamper et al, 2006) and signaling effects (Lim et al, 2016) at low concentrations.…”
Section: Photochemical Reactionsmentioning
confidence: 98%
“…In some cases where the highest occupied molecular orbital (HOMO) is sufficiently deep, oxidation of water as the donor is possible. Unfortunately, often self-oxidation of the organic semiconductor itself will serve to complete the photochemical cycle and lead to irreversible corrosion of the organic semiconductor (Gryszel et al, 2018b;Migliaccio et al, 2018). It was experimentally found that the deeper the HOMO, the more stable the semiconductor is with respect to self-oxidation.…”
Section: Photochemical Reactionsmentioning
confidence: 99%
“…We based the method on our previous work on photocatalysis with organic semiconductor films and particles, [14,22] and for each of the dyes we prepared a set of solutions of different pH and containing different sacrificial electrondonating molecules. We based the method on our previous work on photocatalysis with organic semiconductor films and particles, [14,22] and for each of the dyes we prepared a set of solutions of different pH and containing different sacrificial electrondonating molecules.…”
Section: H 2 O 2 Evolution Experiments With Different Sacrificial Elementioning
confidence: 99%